Knowledge and Practice of Oral Rehydration Solution in Diarrhoea of the Mothers Attending ORT Corner of Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2020)
This cross sectional type of descriptive study was carried out among the mothers, who attended ORT corner of Rajshahi Medical College Hospital for the treatment of diarrhoea of their children to assess their knowledge and practice of oral rehydration solution in diarrhoea. The sample size was 385, which was selected purposively. Data were collected from the respondents by face to face interview according to a partially structured questionnaire. Data were analysed by using SPSS software programme and interpretations were done using appropriate statistical tests like Chi Square Test. Ethical issues were considered throughout the study. Majority (62.5%) of the mothers were in the age group of 21 – 30 years and most (71%) of them were housewives. Most (95.12%) of the mothers knew the preparation of ORS correctly but only 42.82% of them used ORS properly during diarrhoea of their children. The relationship of correct knowledge on ORS preparation was direct with literacy level and monthly family income of the mothers, which were significant (p